Metal complexes of novel Schiff base derived from the condensation of 2‐quinoline carboxaldehyde and ambroxol drug with some transition metal ions. (22nd May 2018) - Mahmoud, Walaa H.; Mohamed, Gehad G.; Elsawy, Hoda A.; Radwan, Mostafa A.
Abstract : A new Schiff base was prepared as the condensation product of the reaction of 2‐quinoline carboxaldehyde and ambroxol drug. The Schiff base ligand thus obtained (HL; trans ‐4‐[(2‐(2‐quinolinoimino)‐3, 5‐dibromobenzyl)amino]cyclohexanol) was further employed as a tridentate ligand for the synthesis of new complexes through reaction with Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) metal ions. The synthesized HL and its metal complexes were characterized using various physicochemical techniques including elemental analysis, Fourier transform infrared and UV–visible spectroscopies, conductimetric and magnetic susceptibility measurements, mass spectrometry and thermal analyses. 1 H NMR data indicated that complex formation was through the amino group rather than the aliphatic hydroxyl group. Thermal analysis gave an idea about the decomposition pattern of HL and its complexes. Also, it revealed the number of water molecules in the inner and outer spheres of the complexes. An octahedral geometry for all the complexes has been suggested. HL and its complexes were screened for their antimicrobial activity against various species of bacteria and fungi using the disc diffusion method. The Cr(III) complex had the highest antimicrobial activity. Abstract : Novel Schiff base HL based on ambroxol drug and its binary metal complexes were characterized by standard physicochemical procedures. HL and its complexes were screened for their antimicrobial activity against various species of bacteria and fungi using the disc diffusion method. The Cr(III) complex had the highest antimicrobial activity. Molecular docking study provided useful structural information for inhibition studies.